(Non)thermal aspects of charmonium production and a new look at [psi] suppression - Braun-Munzinger, Peter; Stachel, Johanna (Arxiv, 2000)
To investigate a recent proposal that J/$ψ$ production in ultra-relativistic nuclear collisions is of thermal origin we have reanalyzed the data from the NA38/50 collaboration within a thermal model including charm. Comparison of the calculated with measured yields demonstrates the non-thermal origin of hidden charm production at SPS energy. However, the ratio $ψ^{'}$/(J/$ψ)$ exhibits, in central nucleus-nucleus collisions, thermal features which lead us to a new interpretation of open charm and charmonium production at SPS energy. Implications for RHIC and LHC energy measurements will be discussed.